Orienting and Emotional Perception: Facilitation, Attenuation, and Interference - Bradley, Margaret M.; Keil, Andreas; Lang, Peter J. (Frontiers in Psychology, 2012)
Human emotions are considered here to be founded on motivational circuits in the brain that evolved to protect (defensive) and sustain (appetitive) the life of individuals and species. These circuits are phylogenetically old, shared among mammals, and involve the activation of both subcortical and cortical structures that mediate attention, perception, and action. Circuit activation begins with a feature-match between a cue and an existing representation in memory that has motivational significance. Subsequent processes include rapid cue-directed orienting, information gathering, and action selection – What is it? Where is it? What to do? In our studies of emotional perception, we have found that measures that index orienting to emotional cues generally show enhanced circuit activation and response facilitation, relative to orienting indicators occasioned by affectively neutral cues, whether presented concurrently or independently. Here, we discuss these findings, considering both physiological reflex and brain measures as they are modulated during orienting and emotional perception.